Environmental and Human Health Risk Assessment of Heavy Metals in Soils from Automobile Mechanic Villages in Enugu State, Nigeria - Emmanual Cukwudi Ugwu; Prisca Ifeoma Udeozo; Okechukwu Paul Nsude; Effiong Imoh; Kingsley John Orie (Asian Journal of Physical and Chemical Sciences, 2026)
Automobile mechanic activities can introduce potentially toxic metals into surrounding soils through the disposal of spent engine oil, metallic scraps, batteries and other vehicle-related wastes. This study assessed heavy metal contamination, ecological risk and potential human-health risks in soils from automobile mechanic villages at Coal Camp and Emene, Enugu State, Nigeria. Soil samples were digested using a nitric acid–perchloric acid mixture and analysed for Cd, Co, Cr, Cu, Fe, Hg, Mn, Ni, Pb and Zn using Atomic Absorption Spectrophotometry (AAS). Contamination and ecological risks were evaluated using the contamination factor (CF), pollution load index (PLI), degree of contamination (Cdeg), modified degree of contamination (mCd), geo-accumulation index (Igeo) and potential ecological risk index (PERI). Human-health exposure was evaluated through dermal contact and soil ingestion using estimated average daily dose (ADD), hazard quotient (HQ), hazard index (HI) and incremental lifetime cancer risk (ILCR). Zinc recorded the highest concentrations at Coal Camp (1.2338 mg/kg) and Emene (1.2327 mg/kg), whereas mercury exhibited the highest contamination and ecological-risk contribution. The highest CF values were recorded for Hg at Coal Camp (10.075) and Emene (7.280), while Igeo values of 2.748 and 2.279 indicated moderate-to-strong Hg pollution, respectively. Coal Camp recorded higher Cdeg (11.270), mCd (1.127), PLI (0.0133) and RI (436.52) than Emene, which recorded Cdeg (8.417), mCd (0.842), PLI (0.0124) and RI (322.98). All HQ and HI values were below 1, indicating low non-carcinogenic risk through soil ingestion. Total ILCR values ranged from 4.882 × 10⁻⁷ to 1.359 × 10⁻⁶, with children showing higher estimated risks than adults. Overall, the soils exhibited low overall metal pollution based on PLI, but Hg represented the principal contaminant of concern and contributed substantially to ecological risk. Improved management of automobile wastes and regular monitoring of mechanic-village soils are recommended.